Significant reduction of inflammation and sebaceous glands size in acne vulgaris lesions after intense pulsed light treatment. Issue 1 (9th September 2016) - Barakat, Manal T.; Moftah, Noha H.; El Khayyat, Mohammad A. M.; Abdelhakim, Zainab A.
Abstract: Intense pulsed light (IPL) has been used for years in treatment of acne vulgaris. However, quantitative evaluation of histopathological changes after its use as a sole therapy was poorly investigated. Accordingly, this study aims to objectively evaluate inflammatory infiltrate and sebaceous glands in acne vulgaris after IPL. Twenty‐four patients of acne were treated with six IPL sessions. Clinical evaluation was done at 2 weeks after last session by counting acne lesions. Patient satisfaction using Cardiff Acne Disability Index (CADI) was recorded at baseline, 2 weeks and 3 months after IPL. Using histopathological and computerized morphometric analysis, quantitative evaluation of inflammatory infiltrate and measurement of surface area of sebaceous glands were performed for skin biopsies at baseline and 2 weeks after last session. After IPL, there was significant reduction of all acne lesions especially inflammatory variety with significant decrease of CADI score at 2 weeks and 3 months after IPL ( p  < .05). Microscopically, there was significant decrease in density of inflammatory infiltrate and surface area of sebaceous glands ( p  < .05). So, IPL is fairly effective therapy in acne vulgaris especially inflammatory variety. The results suggest that IPL could improve acne lesions through targeting both inflammation and sebaceous glands.